Teacher Education and its Relevance to 21st Century Secondary School Education in Nigeria: The Perspective of an Educational Administrator - Ugochukwu Kysburn Agi (European Scientific Journal, ESJ, 2019)
This paper focuses on exploring the relationship between teacher education variables and educational requirements of students in 21st century Nigeria. The correlational research design was adopted in the study. A total of 273 senior secondary school teachers took part in the study. Random sampling technique was used to select the teachers through balloting. A validated researcher designed 47-item instrument which was used for data collection. The reliability of the instrument was established using the Cronbach alpha method to obtain an index of 0.83. Seven research questions and three hypotheses guided the study. Mean, standard deviation, and multiple linear regression analysis were used for data analysis. The findings among others established the fact that the current content of teacher education is relevant in meeting the professional training needs of teachers in the 21st century Nigeria (M=3.12, SD=0.41), the extent of the current content is relevant in meeting best practices of teacher education in 21st century Nigeria (M=2.96, SD=0.50), and the extent of the content of national policy on teacher education is relevant to 21st century Nigeria education (M=2.65, SD=0.56), which were rated above average. The educational requirements of students in 21st century Nigeria was also rated moderately satisfactory (M=2.80, SD=0.44). There were respectively positive, strong, and significant relationships between current content of teacher education (Beta=0.152, t=2.881, prob=0.004), best practices of teaching (Beta=0.146, t=2.884, prob=0.004), teacher education policy (Beta=0.377, t=8.229, prob=0.000) and the educational requirements of students in 21st century Nigeria. It was recommended, among others, that the current content of teacher training programmes should continue to link with the knowledge needed in the 21st century.